2021
DOI: 10.2113/2021/7064502
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grain Size Transition on Flow and Solute Transport through 3D Layered Porous Media

Abstract: Soils and other geologic porous media often have contrasting grain size layers associated with a grain size transition zone between layers. However, this transition zone is generally simplified to a plane of zero thickness for modeling assumption, and its influence has always been neglected in previous studies. In this study, an approach combining a deposition process and a random packing process was developed to generate 3D porous media without and with consideration of the transition zone. The direct numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The obtained experimental results of three groups of porous media indicated that the cementation degree of the solid grains had significant influencing effects on the temporal evolution of the dilution breakthrough curves. As shown in Figure 3, for the porous media in which the solid grains were slightly cemented (PM35, PM30), the values of the (23,43,63, and 84 mm) increased rapidly to levels higher than the asymptotic values of the transient flux-related dilution index in the noncemented porous medium (PM39). In addition, it was found that the higher the cementation degree, the greater the asymptotic value of the flux-related dilution index.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The obtained experimental results of three groups of porous media indicated that the cementation degree of the solid grains had significant influencing effects on the temporal evolution of the dilution breakthrough curves. As shown in Figure 3, for the porous media in which the solid grains were slightly cemented (PM35, PM30), the values of the (23,43,63, and 84 mm) increased rapidly to levels higher than the asymptotic values of the transient flux-related dilution index in the noncemented porous medium (PM39). In addition, it was found that the higher the cementation degree, the greater the asymptotic value of the flux-related dilution index.…”
Section: Resultsmentioning
confidence: 95%
“…For example, incomplete mixing at smaller scales has been found to generally lead to the reaction extent of the solute being lower than the predictions obtained using Darcy-Scale reactive transport models [6]. In addition, previous studies have revealed that the heterogeneity of a porous medium and the characteristics of pore channels, including the topological features, connectivity, and size distributions of pore spaces, have significant influences on solute dilution processes in a porous medium [22][23][24]. In particular, the results of previous studies have indicated a strong link between the enhancement of solute dilution and the flow focusing facilitated by the heterogeneous permeability field in a spatially uncorrelated aquifer [25,26].…”
Section: Introductionmentioning
confidence: 99%